Plasma Deposition of an Organophosphorus Coating at Atmospheric Pressure. Issue 6 (8th April 2013) - Hilt, Florian; Duday, David; Gherardi, Nicolas; Frache, Gilles; Bardon, Julien; Choquet, Patrick
Abstract Plasma polymerisation of an organophosphorus monomer in atmospheric pressure‐dielectric barrier discharge was studied. Phosphate‐based molecules were introduced as a vapour into a nitrogen plasma at atmospheric pressure and a phosphorus‐containing coating was obtained. Scanning electron microscopy and ellipsometry revealed the morphology of the coating while Fourier transform infrared spectroscopy and X‐ray photoelectron spectroscopy indicated a hybrid organic–inorganic coating containing phosphate, organophosphate and different N‐containing groups. The new polymer structure of the coating was highlighted by secondary ion mass spectrometry.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>